Relationship of adipokine to insulin sensitivity and glycemic regulation in obese women: The effect of body weight reduction by caloric restriction - Velojić-Golubović Milena; Dimić Dragan; Antić Slobodan; Radenković Saša; Đinđić Boris; Jovanović Miodrag (Vojnosanitetski Pregled)
Bacground/Aim. Visceral fat is highly active metabolic and endocrine tissue which secretes many adipokines that act both on local and systemic level. It is believed that adipokines and "low-grade inflammatory state" represent a potential link between obesity, metabolic syndrome, insulin resistance and cardiovascular disease. Leptin and adiponectin are considered to be the most important adipokines with the potential metabolic and cardiovascular effects. Body weight loss improves insulin sensitivity and decreases risk for most complications associated with obesity. The aim of this study was to determine the effects of moderate loss of body weight on the level of leptin and adiponectin, insulin sensitivity and abnormalities of glycoregulation in obese women, to determine whether and to what extent the secretory products of adipose tissue, leptin and adiponectin contribute to insulin sensitivity, as well as to assess their relationship and influence on glycemia and insulinemia during the period of losing body weight using a calorie restricted diet. Methods. The study involved 90 obese female subjects (BMI